2014
DOI: 10.1016/j.seizure.2013.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of comprehensive epilepsy education programme for school teachers in Chandigarh city, India

Abstract: The epilepsy intervention educational package provided a positive, short term, impact on the knowledge and skills of teachers about epilepsy. There is a need for regular workshops to improve and reinforce the knowledge and skills of the teachers about health problems like epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 18 publications
3
27
1
1
Order By: Relevance
“…Using a series of workshops on the management of FA in epilepsy, in a study conducted with Indian teachers, it identified that there was a positive impact on the participants. It became evidenced by the increase in score after the intervention, 20 results similar to study in China. 21 To assess its participants during four stages, in which the latter was after four years of training, it got stable knowledge retention.…”
Section: Consideringsupporting
confidence: 78%
“…Using a series of workshops on the management of FA in epilepsy, in a study conducted with Indian teachers, it identified that there was a positive impact on the participants. It became evidenced by the increase in score after the intervention, 20 results similar to study in China. 21 To assess its participants during four stages, in which the latter was after four years of training, it got stable knowledge retention.…”
Section: Consideringsupporting
confidence: 78%
“…A more drastic presentation on the possibility of death might have increased awareness of this. In general, gaining extra Wait and see 16 (13) 17 (14) knowledge can reduce fears, but knowing that a seizure could have a fatal outcome could generate fears and cause adults to overprotect children with epilepsy and reduce social participation (16,17). Children have to be kept out of harm's way, but they also need to participate in their peer group activities as much as possible and teaching programmes should enable teachers to find the right balance.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Teachers are not the only group who need more training in this measure. Half of the teachers rolled the seizing person on their side which needs improvement as it is a life-saving first-aid measure.…”
Section: First-aid Measuresmentioning
confidence: 99%
“…The majority of teachers did not take this measure in some other studies either. 24,25 Teachers are not the only group who need more training in this measure. In a study in Tehran, only 15% of parents positioned their child onto their side during a convulsion.…”
Section: First-aid Measuresmentioning
confidence: 99%